PENGELOLAAN SAMPAH KERTAS MENJADI KERAJINAN TANGAN KESENIAN TRADISIONAL BANDUNG - Bambang Nurcahya, Said; Muksin, Muksin (Jurnal Pengabdian Kepada Masyarakat, 2024)
The city of Bandung is experiencing a waste emergency because the landfill suffered landslides and fires so that for several weeks it could not receive household waste and industrial waste from Bandung residents. The Bandung City Government, in this case the Environmental Agency, has also taken steps to handle waste, including building magot houses in each village in the city of Bandung, but this activity is still carried out by staff and linmas in the village whose duties are already many so that it is still not optimal in handling it. In order to simplify the handling of waste in Bandung, three categories of waste were created: household and environmental waste with green bins, paper waste, wrappers and cans with yellow bins and glass waste, olie, soap, and other hazardous waste with red bins. It is rather difficult to teach waste segregation to the community, especially for those who are accustomed to disposing of waste by putting it together in one place at home, for this reason, researchers invite the community to be involved in caring for waste from households that have been separated into four groups, hazardous waste, plastic cans, household waste, and paper. In this research is more focused on paper waste that is processed into handicrafts in the form of benjang art and derivatives of benjang art.